Субмікронні аерозолі і проблеми побудови системи дозиметричного контролю внутрішнього опромінення персоналу об’єкта Укриття і зони відчуження - Бондаренко, О.О. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2005)
Обговорюється феномен надлишкового внеску субмікронних аерозольних частинок в об¢єкті “Укриття”, який спостерігався в багатьох дослідженнях проведених різними методами й багатьма дослідниками, у контексті розгляду сукупності факторів внутрішнього опромінення персоналу, що визначають систему дозиметричного контролю внутрішнього опромінення персоналу. Відмічено, що останнім часом при розгляді чинників, які визначають формування доз внутрішнього опромінення персоналу об¢єкта “Укриття”, багато уваги приділяється субмікронним аерозолям. При цьому деякі публікації оминають найзначущі чинники, які визначають формування доз і надійність дозових оцінок. Також ігноруються результати інших дослідників аерозолів в об¢єкті “Укриття” й на території зони відчуження. На підставі такого неповного аналізу чинників робиться безпідставний висновок про завищену значимість субмікронних аерозолів при формуванні доз внутрішнього опромінення. Проблема в даний час полягає не стільки в недосконалості існуючих нормативно-методичних документів, а в тому, що на сьогоднішній день існуюча система контролю внутрішнього опромінення на всіх без виключення підприємствах, розташованих на території зони відчуження, не відповідає загальновизнаному світовому досвіду. При цьому основною проблемою є не відсутність підходів, нормативів і фахівців, а відсутність практичної реалізації. Виходячи з вищевикладеного, у роботі запропоновано першочергові технічні заходи для встановлення адекватної системи дозиметричного контролю внутрішнього опромінення персоналу. Рассматривается феномен избыточного вклада субмикронных аэрозольных частиц в объекте "Укрытие", который наблюдался во многих исследованиях, проведенных разными методами и многими исследователями, в контексте рассмотрения совокупности факторов внутреннего облучения персонала, которые определяют вид системы дозиметрического контроля внутреннего облучения персонала. Констатируется, что в последнее время при рассмотрении факторов, которые определяют формирование доз внутреннего облучения персонала объекта "Укрытие", много внимания уделяется субмикронным аэрозолям. При этом некоторые публикации обходят наиболее значимые факторы, определяющие формирование доз и надежность дозовых оценок. Также игнорируются результаты других исследователей аэрозолей в объекте "Укрытие" и на территории зоны отчуждения. На основании такого неполного анализа факторов делается безосновательный вывод о завышенной значимости субмикронных аэрозолей при формировании доз внутреннего облучения. Проблема в настоящее время заключается не столько в несовершенстве существующих нормативно-методических документов, а в том, что на сегодняшний день существующая система контроля внутреннего облучения на всех без исключения предприятиях, расположенных на территории зоны отчуждения, не отвечает общепризнанному мировому опыту. При этом основной проблемой является не отсутствие подходов, нормативов и специалистов, а отсутствие практической реализации. Исходя из вышеизложенного, в работе предложены первоочередные технические меры для установления адекватной системы дозиметрического контроля внутреннего облучения персонала. This publication is dedicated to discussion of the phenomenon of the elevated contribution of submicron aerosol particles inside the оbject "Ukryttya", which was observed in many research conducted by different methods and many researchers, in context of consideration the whole set of factors of internal exposure of the personnel, which determine the structure of the internal dose monitoring system. It can be noted that recently a lot of attention are paid to the submicron aerosols during consideration of internal dose forming factors for the оbject "Ukryttya" personnel. At the same time some publications omit other meaningful factors determining internal doses and reliability of dose estimations such as: the ratio of the concentration at a sampling place of and in the breathing area, protection factor of respirators, statistical stability of the radionuclide ratio (especially ¹³⁷Cs to transuraniums), type of system intake, etc. Sometimes results of other researchers concerning aerosols in the оbject "Ukryttya" and at the territory of the Exclusion zone are also ignored. On a basis of such incomplete analysis of factors a groundless conclusion about the highest meaningfulness of submicron aerosols for internal dose formation is drawn. Indeed, the phenomenon of submicron particles inside the оbject "Ukryttya" requires the additional and deep studying by different and independent groups of researchers with the use of various physical principles. Only after complex comparison of results of such research it will be possible to draw out a final conclusions (not only qualitative but also quantitative one). Presently a problem consists not so much in imperfection of existent normative and methodical documents, but that today the internal dose monitoring system existent at all without exception enterprises located at the Exclusion zone does not meet internationally accepted experience. Thus a basic problem is not in absence of approaches, norms or specialists, but in absence of practical realisation. In this context appearance of Protocol of internal dose monitoring the оbject "Ukryttya" personnel is a definitely progressive step to construction of an integral system of radiation safety not only for the оbject "Ukryttya" but also for the Exclusion zone as a whole. Coming from the aforementioned, a set of high priority technical measures for establishment of an adequate internal dose monitoring system is suggested.